Необхідність запровадження воєнної парадигми податкового права України в умовах воєнного стану - Дутчак, Остап (My University, 2024)
The article examines the factors which necessitated the introduction of the martial law paradigm of tax law of Ukraine. The main methodological tools for analyzing the problem are the axiological and anthroposociocultural approaches, general scientific principles of historicism and objectivity, functional and systematic methods of processing empirical and theoretical material. Particular attention is paid to identifying and comprehending the cumulative effect of qualitatively distinguished groups of factors that necessitated the introduction of the martial law paradigm of Ukrainian tax law under martial law. As a result of a comprehensive and deep comprehension of the above-mentioned issues, the author substantiates the following conclusions: Russia's full-scale war against Ukraine has paradigmatically changed the hierarchy of all public and private needs of every Ukrainian, Ukrainian society as a whole and the Ukrainian State, their nature, sources and conditions for their satisfaction. The need to ensure real security, the right to life and dignity for each of the above-mentioned subjects has become a priority and, at the same time, common to all of them. This security need has acquired an absolute and existential character; it cannot be postponed in its solution or satisfied in parts. The aforementioned need has been transformed into a criterion for the legitimacy of the use of public financial resources, primarily the State Budget of Ukraine, as well as its extraordinary content, by the Ukrainian state as a whole, its authorities and local self-government bodies, and their officials. The above factors, taken together, violated the paradigmatic principles of public finance functioning, went beyond the pre-war concepts of their standards, and, together with new fiscal risks for public finance, led to the introduction of the military paradigm of Ukrainian tax law.